Integrating literature lessons with the subject of mother tongue teaching - Khasanovna, Niyozmetova Roza; Farkhodovna, Fozilova Mohigul (Linguistics and Culture Review, 2021)
In order to differentiate literary-speech competencies in literature lessons, the article develops the features of oral speech characterized by orthographic norms, other than biblical (written) speech, based on the norms of pronunciation and spelling of language phenomena studied in the native language. Thus, in literature classes, the relevant knowledge, skills, and competencies for the formation of types of speech activities at the level of competencies can be acquired on the basis of knowledge of the different aspects of these competencies. Competences related to the types of speaking activities require to pay attention to the method of speech as the most important of the specific features of oral and written speech, to this end, to integrate the subject of literature with the mother tongue from the educational content. “Interdisciplinary connections of the Russian language and literature are carried out at all lessons of speech development in the following directions: 1) the formation and consolidation of knowledge and skills of students in functional stylistics, necessary for the correct organization of speech activity in various genres of oral and written statements; 2) teaching common for these subjects types of oral and written speech activities.